Obesity among poor Americans : is public assistance the problem? - Smith, Patricia K. (Patricia Kay), 1959- (Vanderbilt University Press, 2009)
This book investigates the controversial claim by welfare critics that public assistance programs like the Food Stamp and National School Lunch programs contribute to obesity among the poor. The author synthesizes empirical evidence from an array of disciplines--anthropology, economics, epidemiology, marketing, medicine, nutrition science, psychology, public health, sociology, and urban planning--to test this claim and to test whether other causal processes are at work. --from publisher's description.